Psychometric Testing of Oldenburg Burnout Inventory among Academic Staff in Pakistan - Anwar Khan; Rosman Bin Md Yusoff (International Review of Management and Marketing, 2016)
Burnout is an emerging concept of twenty first century. Its measurement and assessment has attracted the interest of scientists around the globe. Social scientists, particularly faced problems in deciding the dimensions of burnout. The most commonly used Maslach Burnout Inventory has three dimensions, however, there are more negatively coded items in this inventory that can undermine its validity. In response Oldenburg Burnout Inventory was developed with a uniform number of negative and positive items. It has been tested among different populations around the world with good factors structure, but it has not been tested in academia of Pakistan, especially among a diverse population of teaching staff. The current study aims at Econometric testing of Oldenburg Burnout Inventory followed by its distribution among 450 academic staff working in six universities of Pakistan. A cross-section research design was applied. The reliability was checked through calculating inter items statistics, i.e. Cronbach Alpha & Pearson correlation coefficients, while the construct validity was determined by running Factor Analysis. The reliability analysis showed that all items had mean Cronbach Alpha Coefficient of Σα= 0.83, whereas items-total correlations ranged up to r=0.62, which is evidence of its internal consistency. The results of Exploratory Factor Analysis revealed that that factor loadings ranged from 0.57 to 0.90. Similarly, the results of Confirmatory factor analysis showed that two-factor model demonstrated better fit as compared to one-factor model. The detailedEconometric analysis confirmed that Oldenburg Burnout Inventory is a reliable and valid tool for measurement of burnout in academia of Pakistan, thus it could also be successfully used in different working sectors of Pakistan for the assessment of Burnout. The findings of the current study are valuable additions into the existing body of knowledge and empirical research on the burnout inventories.